2013
DOI: 10.1029/2012ja017918
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal variation of the daily mean thermospheric mass density

Abstract: [1] This study uses the GRACE (Gravity Recovery And Climate Experiment) and CHAMP (CHAllenging Minisatellite Payload) accelerometer measurements from 2003 to 2008. These measurements gave thermospheric mass densities at~480 km (GRACE) and~380 km (CHAMP), respectively. We found that there are strong longitude variations in the daily mean thermospheric mass density. These variations are global and have the similar characteristics at the two heights under geomagnetically quiet conditions (Ap < 10). The largest re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…Similar results have been pictured in Xu et al . [], with a hemispherically asymmetric distribution, showing higher values near the magnetic poles. Previous studies using PCA techniques [ Matsuo and Forbes , ; Lei et al ., ] provided no clear descriptions for these features.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been pictured in Xu et al . [], with a hemispherically asymmetric distribution, showing higher values near the magnetic poles. Previous studies using PCA techniques [ Matsuo and Forbes , ; Lei et al ., ] provided no clear descriptions for these features.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning longitudinal variations, Xu et al . [] revealed from CHAMP and GRACE accelerometers a hemispherically asymmetric distribution, positive always near the magnetic poles and with strong seasonal variations.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the background neutral composition is not the same in each hemisphere; it may not be distributed uniformly with longitude and latitude and have hemispheric asymmetry as reported by Xu et al . []. Such changes in neutral composition will also lead to changes in electron density even if the particle precipitation energy flux is the same in each hemisphere.…”
Section: Resultsmentioning
confidence: 99%
“…Kwak et al (2012) similarly found that nonmigrating tides in CHAMP data are dominated by the DE3 and DE2 modes, as well as SPW4 variations. Xu et al (2013) studied the longitude dependence of diurnally averaged CHAMP and GRACE data (essentially the superposition of stationary tidal modes), and found the largest variations at summer high latitudes, with peak amplitudes of ~10% (CHAMP) and ~15% (GRACE) occurring near the geomagnetic poles. The pattern is presumably associated with the corresponding longitude dependence of magnetospheric heating.…”
Section: Nonmigrating Tides and Longitude Dependencementioning
confidence: 99%
“…Thermospheric density longitudinal variations, whose amplitude at 400 km altitude can average up to 10%, are forced by patterns of net tropospheric heating (X. Zhang et al, 2010), momentum and energy exchange with the magnetically constrained ionosphere Xu et al, 2013), and nonlinear tide-tide interactions (Angelats i Coll and . used exospheric temperature variations derived from CHAMP and GRACE data to infer a connection between DE3 and DE2 thermal tides in the troposphere and thermosphere.…”
Section: Nonmigrating Tides and Longitude Dependencementioning
confidence: 99%